Strengthened of a Square RC Columns using BFRP and GFRP: The Experimental Investigations - Patel, Tejash; Salla, Sanjay; Vasanwala, Sandip; Modhera, Chetankumar (Trends in Sciences, 2022)
Reinforced concrete (RC) columns, jacketing of FRPs has become a standard strengthened technique in the present times. The current research scenario focuses on the fact that strengthened and rehabilitation of RC columns by CFRP and GFRP are more effective. Additionally, the present research also highlights a new class of natural composites of BFRP (Basalt Fiber Reinforced Polymer) bonded with adhesive to column specimens as an alternate confinement material. Generally, it is advisable to use RC columns instead of CFRP and GFRP confinement material. The experimental study was strengthened by partially and fully wrapped square RC columns using GFRP and BFRP uni - directional and bi-directional. The behavior of stress-strain curves and failure modes were observed. The experimental results show that the substantial increment in ultimate load-displacement capacity, ultimate stress-ultimate axial and lateral strains lead to BFRP and GFRP failure. The fully warped square reinforced concrete (RC) column performs better in getting stress-strain behavior and displacement limit as compared to the partially covered system. It is a fact that the strengthened obtained by partial wrapping with BFRP and GFRP is a preferable and cost-effective alternative as compared to the fully wrapped. The test results show that the CNR-DT-R1 model is more reliable than Lam & Tang and provides reasonable and precise calculations for the ultimate axial stress of partially and fully wrapped RC columns. HIGHLIGHTS Now days strengthening and rehabilitation of RC columns by CFRP and GFRP is more effective, but the natural composite BFRP is also an alternative confinement material The experimental study was strengthened by partially and fully wrapped square RC columns using GFRP and BFRP Uni - directional and bi-directional The behaviour of stress-strain curves and failure modes were observed. The experimental results show that the substantial increment in ultimate load-displacement capacity, stress, axial and lateral strains lead to BFRP and GFRP failure The study has been performed to verify the experimental data’s reliability and accuracy with the theoretical models such as CNR-DT R1 and Lam & Teng model GRAPHICAL ABSTRACT